2018
DOI: 10.1186/s40560-018-0290-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional overdistension during prone positioning in a patient with acute respiratory failure who was ventilated with a low tidal volume: a case report

Abstract: BackgroundProne positioning may provide a uniform distribution of transpulmonary pressure and contribute to prevent ventilator-induced lung injury. However, despite moderate positive end-expiratory pressure and low tidal volumes, there is still a risk of regional overdistension.Case presentationA man with refractory hypoxemia was mechanically ventilated with prone positioning. Although prone positioning with a plateau pressure of 18 cmH2O and a positive end-expiratory pressure of 8 cmH2O promptly improved oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This intervention influences regional lung ventilation by changing the body position. The previous studies have used EIT to monitor the ventilation improvement during the body position changes ( 4 6 , 28 , 29 ) and have proven the feasibility of EIT. Hough et al ( 4 ) confirmed that body position changes might influence the regional ventilation distribution in infants, whereas van der Burg et al ( 5 ) did not find any differences between the lateral and supine positions.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention influences regional lung ventilation by changing the body position. The previous studies have used EIT to monitor the ventilation improvement during the body position changes ( 4 6 , 28 , 29 ) and have proven the feasibility of EIT. Hough et al ( 4 ) confirmed that body position changes might influence the regional ventilation distribution in infants, whereas van der Burg et al ( 5 ) did not find any differences between the lateral and supine positions.…”
Section: Discussionmentioning
confidence: 99%
“…Early mobilization in uences regional lung ventilation by body position changing. Previous researches have used EIT to monitor ventilation improvement during body position changing [23][24][25][26][27] and proved EIT's feasibility. Hough et al [24] con rmed that body position changes might in uence regional ventilation distribution in infants, whereas Pauline S et al [25] reported no difference between lateral and supine positioning.…”
Section: Eit On Regional Lung Ventilationmentioning
confidence: 99%
“…A recent clinical case reported HENC could cause pulmonary hyperinflation with mild pneumomediastinum assessed by high-resolution chest computed tomography scan [8] in a patient with bronchiolitis obliterans syndrome. Moreover, Kotani et al reported the regional overdistension was detected at a prone position in an ARDS patient with a low tidal volume [9]. We proposed a novel EIT method to assess lung overdistension in the spontaneous breath condition [1].…”
Section: Huaiwu He Yun Longmentioning
confidence: 99%